"Diam Adalah Emas": Ekslusivitas Tafsir pada Term yang Tidak Diterjemahkan dalam Tafsir Al-Mishbah Karya M. Quraish Shihab - HS, Muhammad Alwi (SUHUF, 2023)
This article aims to discuss the exclusivity of tafsir on terms not translated by M. Quraish Shihab (MQS) in Tafsir Al-Misbah, especially to the terms caliph (al-Baqarah/2: 30), ummatan wasaṭān (al-Baqarah/2: 134), qawwāmūn (an-Nisa/4: 34), awliyā’ (al-Maidah/5: 51), and jilbāb (al-Ahzab/33: 59). The main argument of this article is that not translating a term of the Qur’an indicates the idiosyncrasies of that term, just as the expression ‘silence is golden’. This article uses the descriptionanalytical method, based on a qualitative approach. The results of this article show that the interpretation of MQS leads to two important things. First, the term has a variety of meanings among scholars-interpreters. Second, the emergence of meaning from the other party who wants to be criticized or raises a different meaning. The exclusivity of MQS exegesis arises as an attitude towards the socio-religious topics discussed in its tafsir. This article implies that not translating can be an alternative to an exegetical reception of Qur’anic terms, especially those with sensitivity and a variety of meanings.